A Multi-Image Cryptosystem Using Quantum Walks and Chebyshev Map. (18th October 2021) - Abd-El-Atty, Bassem; Iliyasu, Abdullah M.; Abd El-Latif, Ahmed A.
Abstract : The ubiquity of image and video applications in our daily lives makes data security and privacy prominent concerns for everyone. Among others, various image cryptosystems are relied upon to provide the necessary safeguards. With the inevitable realisation of quantum computing hardware, however, the anticipated quantum supremacy entails effortless violation of the integrity of even the best cryptosystems. Quantum walks (QWs) utilise the potent properties of quantum mechanics to provide randomness via stochastic transitions between states. Our study exploits these properties of QWs to design a multi-image cryptosystem. Furthermore, we infuse the symmetricity and orthogonality of Chebyshev maps into the QWs to realise a powerful cryptosystem that guarantees data integrity, authentication, and anonymity of the resulting images. These properties are validated via extensive simulation-based experiments that produce average values of NPCR as 99.606%, UACI as 33.45%, global entropy as 7.9998, and chi-square test as 238.14. Therefore, the proposed cryptosystem provides ordnance to protect images from illicit tampering during the era.